Mucopolysaccharidosis Type II with Inguinal Hernia - Rayamajhi, A; Pokharel, P J; Chapagain, R; Rayamajhi, A K (Journal of Nepal Health Research Council, 2014)
Mucopolysaccharidosis Type II (Hunter syndrome) is a rare X-linked recessive storage disorder caused by deficiency of lysosomal enzyme iduronate-2-sulfatase, causing excess accumulation of glycosaminoglycans in the lysosomes resulting in cellular damage, organ failure and death. Severe subtype develops characteristic clinical features and cognitive impairment early and die in second decade of life. In a resource poor setting, we report a case of Hunter syndrome, severe subtype, based on global development delay, coarse facies, short stature, hepatosplenomegaly and dysostosis multiplex on X-ray with unusual large congenital inguinal hernia. The diagnosis was important because of risk of recurrence of hernia after repair.Keywords: glycosaminoglycans; Hunter syndrome; iduronate-2-sulfatase deficiency; inguinal hernia; mucopolysaccharidosis.